Pengaruh Keputusan Investasi, Kebijakan Deviden, serta Keputusan Pendanaan terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Sartini, Luh Putu Novita; Purbawangsa, Ida Bagus Anom (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 2 Tahun 2014, 2015)
Thi s study aimed to examine effect of  investment decisions, dividend policy and financing deci sions on f irm value  of   manufacturing  companies.   Thi s  research  was  conducted  at  Indonesia  Stock  Exchange  (BEI)  with r esear ch  period  of  2009-2011.  The  amount  of  sample  was  20  companies.  The  sampling  method  used  was purposive  sampling  method.  Analysis  technique  used  in  this  research  was  path  analysis.   The  results  show that   Investment   decisions  has  signif icant   posit ive  effects  on  dividend  policy,   investment  decisions  was significant posit ive effect s on  firm  value, dividend pol icy signif icant positive effect to firm value, f inancing decisions  significant  posi tive  affects  to  firm  value,  and  dividend  policy  has  signi ficant  positive  ef fect    on financing  decisions
Keywords: f irm value, investment decision, dividend pol icy,f inancing decision